Warps Induzidos pela interação com satélites em galáxias barradas simuladas - Wille, Andressa (2024)
Warps are common vertical asymmetries that appear in the outer parts of the galactic discs, bending one part upwards and the other downwards. Many mechanisms can trigger warp formation, including tidal interactions. The interactions with satellites distort mainly the edges of the disc and can also change the central morphology, impacting, for example, the development of a galactic bar. In mergers events, the bar can be weakened or even destroyed. In this study, we aim to compare barred and non-barred galaxy models and their susceptibility to warping. To analyze the effects of induced warps, we used -body simulations of a barred and a non-barred central galaxy interacting with satellites of varying masses (0.1 × 1010M⊙, 0.5 × 1010M⊙ and 1 × 1010M⊙) and initial orbital radii (10, 20 and 30 kpc). We also ran isolated simulations of the central galaxies for comparison. We found that the induced warps are stronger in the barred galaxy compared with the non-barred galaxy, in perturbed and isolated models. In addition, the masses of the satellites determine the level of destruction of the bar and the intensity of the induced warp. The time in which the bar will be weakened or destroyed depends on the orbital radius of the satellite.